The induction of the ovulatory period - Seegar Jones, Georgeanna (2015)
Two powerful instruments -the human gonadotropin and clomiphene-- citrate are at our disposal for the induction of ovulation period in all patients who show an anovulatory period of central origin: psychogenic, neurogenic and pituitary. These drugs must not be used without a prior study of the etiology excluding not only the peripheral fault OVO rich but also the end-organ failure. They are not used in cases of amenorrhea due to intermediary causes as chronic diseases, metabolic diseases -tiroides, adrenol, pancreas and nutritional conditions factors. To avoid complications that are polycystic ovaries and multiple pregnancies, one has to use the minimum effective dose. This dose is, to some extent, based on a single criterion. If these precautions are taken properly, one can expect to improve the outcome of difficult cases such as amenorrhea caused by neurogenic factors and pituitary, hypothalamic amenorrhea and perhaps eradicate the surgical treatment of Stein-Leventhal syndrome.